2020
DOI: 10.1590/0103-8478cr20190718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of encapsulated sodium butyrate and phytogenic on growth performance, carcass traits and health of growing-finishing pigs

Abstract: The aim of this study was to evaluate two feed additives, one based on encapsulated sodium butyrate (Adimix® Precision) (AD) and the other, a phytogenic (Apex® 5) (AX), associated or not with an antimicrobial growth promoter (tylosin) during the growth and finishing phases on performance, carcass characteristics and health conditions. A total of 300 barrows and females were distributed in six treatments in a randomized block design with ten replicates. The treatments consisted of a negative control (NC), posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A multitude of studies about effects of phytogenics on swine growth and health have been also investigated. For instances, a recent study reported that pigs fed diets with a phytogenic mixture (including garlic oil, cinnamic, aldehyde, thymol, carvacrol and eugenol) and/or encapsulated sodium butyrate increased ADG and FCR [113]. An earlier study also showed that piglets fed with herbal extracts (sage, lemon balm, nettle, and purple coneflower) grew faster than control animals and showed significantly higher final average body weights.…”
Section: Phytogenicsmentioning
confidence: 99%
“…A multitude of studies about effects of phytogenics on swine growth and health have been also investigated. For instances, a recent study reported that pigs fed diets with a phytogenic mixture (including garlic oil, cinnamic, aldehyde, thymol, carvacrol and eugenol) and/or encapsulated sodium butyrate increased ADG and FCR [113]. An earlier study also showed that piglets fed with herbal extracts (sage, lemon balm, nettle, and purple coneflower) grew faster than control animals and showed significantly higher final average body weights.…”
Section: Phytogenicsmentioning
confidence: 99%